The Democratic Republic of Congo : Can Incentives to Take Home Textbooks Increase Learning? - World Bank (World Bank, Washington, DC, 2020)
The Results in Education for All Children (REACH) Trust Fund at the World Bank funded an evaluation that measured the effectiveness of both financial and non-financial incentives at the student, classroom, and school levels in the Democratic Republic of Congo (DRC). A new classroom routine was designed to encourage all grades 5 and 6 students to take home a classroom textbook and use it to study for a weekly quiz. Students and schools were incentivized to adopt the routine through a combination of both financial incentives at the group level and non-financial incentives at the individual level. These incentives were implemented by Cordaid (Caritas Netherlands), a Dutch NGO that has operated an RBF project in the South Kivu region of the DRC since 2008. The evaluation found that the incentives given to encourage students to take home textbooks raised their French language test scores by 0.27 to 0.30 standard deviations (SD) but had no significant impact on math test scores.